Bacterial intoxication evokes cellular senescence with persistent DNA damage and cytokine signalling - Blazkova, Hana; Krejcikova, Katerina; Moudry, Pavel; Frisan, Teresa; Hodny, Zdenek; Bartek, Jiri (Journal of cellular and molecular medicine, 2010)
Cytolethal distending toxins (CDTs) are proteins produced and secreted by facultative pathogenic strains of Gram-negative bacteria with potentially genotoxic effects. Mammalian cells exposed to CDTs undergo cell type-dependent cell-cycle arrest or apoptosis; however, the cell fate responses to such intoxication are mechanistically incompletely understood. Here we show that both normal and cancer cells (BJ, IMR-90 and WI-38 fibroblasts, HeLa and U2-OS cell lines) that survive the acute phase of intoxication by Haemophilus ducreyi CDT possess the hallmarks of cellular senescence. This characteristic phenotype included persistently activated DNA damage signalling (detected as 53BP1/gammaH2AX(+) foci), enhanced senescence-associated beta-galactosidase activity, expansion of promyelocytic leukaemia nuclear compartments and induced expression of several cytokines (especially interleukins IL-6, IL-8 and IL-24), overall features shared by cells undergoing replicative or premature cellular senescence. We conclude that analogous to oncogenic, oxidative and replicative stresses, bacterial intoxication represents another pathophysiological stimulus that induces premature senescence, an intrinsic cellular response that may mechanistically underlie the 'distended' morphology evoked by CDTs. Finally, the activation of the two anticancer barriers, apoptosis and cellular senescence, together with evidence of chromosomal aberrations (micronucleation) reported here, support the emerging genotoxic and potentially oncogenic effects of this group of bacterial toxins, and warrant further investigation of their role(s) in human disease.
Keywords: stárnutí buněk; poškození DNA; Haemophilus ducreyi; fenotyp; Phenotype; DNA Damage; Cell Line, Tumor; cytokiny; signální transdukce; Cellular Senescence; Signal Transduction; lidé; Humans; Cell Cycle; Bacterial Toxins; Cytokines; Cyclin-Dependent Kinases; buněčný cyklus; nádorové buněčné linie; cyklin-dependentní kinasy; bakteriální toxiny